2009
DOI: 10.1155/2009/281561
|View full text |Cite
|
Sign up to set email alerts
|

Synapse Plasticity in Motor, Sensory, and Limbo-Prefrontal Cortex Areas as Measured by Degrading Axon Terminals in an Environment Model of Gerbils (Meriones unguiculatus)

Abstract: Still little is known about naturally occurring synaptogenesis in the adult neocortex and related impacts of epigenetic influences. We therefore investigated (pre)synaptic plasticity in various cortices of adult rodents, visualized by secondary lysosome accumulations (LA) in remodeling axon terminals. Twenty-two male gerbils from either enriched (ER) or impoverished rearing (IR) were used for quantification of silver-stained LA. ER-animals showed rather low LA densities in most primary fields, whereas barrel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 111 publications
1
10
0
Order By: Relevance
“…It seems, in fact, that in CD1 mice CA3 and CA1 also exhibit intrinsic plasticity. This assumption finds support in recent findings of a systematic analysis of synaptic turnover rates in diverse cortical areas of the gerbil, showing that associative cortical areas also display synaptic remodeling, and region—as well as layer-specific differences which appear mainly determined by local and distant associative connections [7]. These layer-specific differences were leveled after environmental deprivation during rearing, an effect that parallels our findings after wheel running in CD1 mice.…”
Section: Discussionsupporting
confidence: 91%
“…It seems, in fact, that in CD1 mice CA3 and CA1 also exhibit intrinsic plasticity. This assumption finds support in recent findings of a systematic analysis of synaptic turnover rates in diverse cortical areas of the gerbil, showing that associative cortical areas also display synaptic remodeling, and region—as well as layer-specific differences which appear mainly determined by local and distant associative connections [7]. These layer-specific differences were leveled after environmental deprivation during rearing, an effect that parallels our findings after wheel running in CD1 mice.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, dopamine receptor activation has been proved to mobilize the striatal neuronal cytoskeleton and modulate GABA neuron migration in the basal forebrain, supporting the result of an increased mesotelencephalic intranetwork r Chou et al r r 1580 r connection [Crandall et al, 2007]. Finally, concomitant higher ability to display synaptic rewiring and changes in the dendritic arborization in the limbic system than in neocortex, eventually increasing interregional morphometric correlations in caudate-limbic network [Butz et al, 2009;Neufeld et al, 2009]. We believe dopamine depletion in PD may, therefore, force neuron remodeling and structural plasticity in both its modulated region and their downstream areas [Braak et al, 2000].…”
Section: Discussionmentioning
confidence: 88%
“…There are also regional differences in the capacity to show structural plasticity. It has been reported that structural plasticity (i.e., synaptic turnover or rewiring, and changes in the dendritic arborization or spine density) is much more frequently observed in limbic regions than in the prefrontal, motor and sensory cortices (Butz et al, 2009;Kolb et al 2003;Neufeld et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, such regional differences in the capacity to show structural plasticity seem to be mediated by the presence of particular neurotransmitters, which may act as neurotrophic factors. Structural plasticity in prefrontal and limbic cortices depends on optimal dopamine levels (Neufeld et al 2009), and, in humans, structural covariance between the neostriatum and the dorsolateral prefrontal cortex is increased in the carriers of a specific haplotype of a protein (DARPP-32) related to molecular mechanisms of dopaminergic neurotransmission (Meyer-Lindenberg 2009).…”
Section: Discussionmentioning
confidence: 99%